Systematic Review and Meta-Analysis of the Effect of Perineural Catheters in Major Lower Limb Amputations. (August 2021) - Laloo, Ryan; Ambler, Graeme K.; Locker, Dafydd; Twine, Christopher P.; Bosanquet, David C.
Abstract : Objective: Controlling pain after major lower limb amputation (MLLA) is of critical importance to patients and clinicians. The aim of this systematic review and meta-analysis was to assess the effect of perineural catheters (PNCs) on post-operative pain, post-operative morphine requirement, in-hospital mortality, long term phantom limb pain, and chronic stump pain. Methods: A systematic review using PubMed, EMBASE via OVID and the Cochrane library from database inception (1946) to 20 October 2020 was performed according to PRISMA guidelines. Studies involving patients undergoing MLLA which reported on post-operative morphine requirement, pain scores, in-hospital mortality, phantom limb pain (PLP), and chronic stump pain were included. Studies comparing PNC use with epidural or wound site local anaesthetic infusions were excluded. Outcome data were extracted from individual studies and meta-analysis was performed using a random effects (Mantel-Haenszel) model for dichotomous data using an odds ratio (OR) summary statistic with 95% confidence intervals (CI), and with an inverse variance random effects model for continuous data using a standardised mean difference (SMD) summary statistic with 95% CIs. Sensitivity analyses were performed for post-operative pain scores and post-operative morphine requirement. Study quality was assessed using the Downs and Black score, and outcomes were assessed using the GRADE tool. Results: Ten studies reporting on 731 patients were included, with 350 patients receiving a PNC and 381 receiving standard care. PNC use is associated with a reduction in post-operative pain (SMD −0.30, 95% CI −0.58 – −0.01, p  = .040, I 2  = 54%, GRADE quality of evidence: low) and post-operative morphine requirements (SMD −0.63, 95% CI −1.03 – −0.23, p  = .002, I 2  = 75%, GRADE quality of evidence: moderate), although the effect of PNC on reduced post-operative morphine requirements is lost on sensitivity analysis of randomised trials only ( p  = .40). No demonstrable effect was found on in-hospital mortality, PLP, or chronic stump pain (GRADE quality of evidence: low). Conclusion: PNC use in amputees is associated with a significant reduction in post-operative pain scores and post-operative morphine requirements, although this latter finding is lost on sensitivity analysis of randomised trials only.